Pengaruh Etika Bisnis Islam dan Kualitas Produk Terhadap Kepuasan Konsumen pada Usaha Base Camp Coffe Kota Bima - Imansyah, Imansyah; Rafiuddin; Dinah Husniah; Muhammad Rasyad Al-fajar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of Islamic business ethics and product quality on customer satisfaction at the Base Camp Coffee business in Bima City. Islamic business ethics used as the basis for business operations include principles such as honesty, justice, and social responsibility, while product quality is measured by taste, presentation, and service provided. The method used in this research is a survey with the distribution of questionnaires to consumers who have visited Base Camp Coffee. The collected data were analyzed using multiple linear regression techniques to determine the relationship between these variables. The results showed that Islamic business ethics and product quality have a significant effect on customer satisfaction. Good implementation of Islamic business ethics is able to create consumer trust and loyalty, while well-maintained product quality increases the positive experience received by consumers. The conclusion of this study is that to increase customer satisfaction, Base Camp Coffee needs to continue to apply appropriate Islamic business ethics and maintain and improve the quality of the products offered.